On the correlation between the enantiomeric excess of L-isovaline and the level of aqueous alteration in carbonaceous meteorites - Avnir, David (Frontiers in Astronomy and Space Sciences, 2024)
A positive correlation was observed between the enantiomeric excess (ee) of L-isovaline (L-iVal) and the degree of aqueous alteration (AqA) of carbonaceous meteorites. The origin of this remarkable phenomenon has remained enigmatic from two points of view: First, the correlation is between seemingly unrelated observables–nothing about AqA is of chiral characteristics; and second, following the accepted assumption that circularly polarized light (CPL) was the origin of the observed meteoritic ee of L-amino acids (AAs), it remined unclear why some of the observed levels of the ee of L-iVal in that correlation are significantly higher than those observed in laboratory simulations or those obtained from circular dichroism (CD) g-factor calculations. The current proposition accounting for this picture attributes late AqA conditions of the meteoritic parent bodies as providing the grounds for amplification of early initially CPL-generated low levels of L-ee. For reasons summarized below, this interpretation, which treats the CPL event and the AqA process as occurring in wide-time separated eras, is re-visited. An alternative interpretation of the observed correlation and of the high ee-values, is provided. It focuses on hydrophilic dust-aggregates clouds in wet star-forming regions in early pre-solar times, where both the CPL event and the grounds leading to the later AqA processes of the parent bodies, occurred. This mechanism removes the time separation between the initial ee formation and the AqA of the parent body, and replaces it with parallel processes, providing a scenario to the observation of high ee’s without total destruction, and to the apparent AqA/L-ee correlation. Although iVal is at the focus of this report, the steps of the development of the alternative mechanism and the conclusions that arise from it, are relevant and applicable to the general observations of L-ee’s of meteoritic AA’s.